Test Piece With Double Path Runner System Using Magnesium Molten For High Precision Die-Casting Products - Tan, Ger Lian (Universiti Malaysia Sarawak (UNIMAS), 2018)
High pressure die casting is a manufacturing process used to produce complex and precise products where molten material is injected into the mold cavity at a very high speed and pressure. Magnesium molding manufacturing are gradually increasing due to the demand on lightweight and sustainable material. Magnesium has several unique physical properties that is comparable with Aluminium metal. Researches indicates that magnesium metal and its alloys are biodegradable, it has a huge potential to be utilized in biomedical field. In this research, we investigated the potential defects location on a mold cavity and modified correspondingly. The design of cavity in this project is a ‘test piece’, an inspection instrument. Design modelling and relevant parameter is input into ANSYS software for numerical simulation. Novelty runner and gate design (Double Path Runner System) to enhance fluid behavior inside the cavity are discussed in this paper.